Pulmonary Kaposi's sarcoma in Africa. Issue 9 (September 1992) - Pozniak, A L; Latif, A S; Neill, P; Houston, S; Chen, K; Robertson, V
Abstract : BACKGROUND: A study was carried out to identify the main clinical radiological and bronchoscopic features of HIV related Kaposi's sarcoma of the lung in African patients. METHODS: Forty seven HIV positive patients with epidemic Kaposi's sarcoma who had clinical or radiological respiratory changes were investigated by simple lung function tests and fibreoptic bronchoscopy. RESULTS: The most common respiratory symptoms in the 47 patients were persistent cough in 42, haemoptysis in 23, and breathlessness in 38. A restrictive spirometric pattern was most common. The mean (SD) forced expiratory volume in one second (FEV1) was 1.88 (0.62) 1 with a forced vital capacity (FVC) of 2.66 (0.87) 1 and a FEV1/FVC% of 73.2 (7.5). On the chest radiograph 26 patients had diffuse reticulonodular shadows, 11 focal nodular shadows, seven a pleural effusion, and one a substantial increase in vascular markings; in two the radiograph was normal. At bronchoscopy characteristic discrete lesions were easily visible in 37 patients and were often bright red. Multiple nodules were seen in 11, flat or early plaque lesions in 12 (14 had both), proximal flat lesions and diffuse infiltration in three, diffuse infiltration alone in four, and masses in two; one had normal appearances at bronchoscopy. One patient had Pneumocystis carinii and two had a single bacterial pathogen cultured from the bronchoalveolar lavage fluid. Only two of 29 bronchoscopic biopsies showed classical histological Kaposi's sarcoma. After cytotoxic treatment 20 patients have died, with an overall median survival of 70 days. CONCLUSION: In this African population symptomatic pulmonary Kaposi's sarcoma was common, with lesions seen in all but one patient at bronchoscopy. Coexistent infection was uncommon. Prognosis was poor despite treatment.